Electrophotographic member, thermal fixing apparatus, and electrophotographic image forming apparatus

By reducing the degree of silicon rubber cross -linking and reducing the initial hardness in advance, the problem of improving the hardness increased by the existing fixed shadow components when the thermal conductivity is increased, and the low -hardness and high durability of the fixed shadow component is realized.

CN119376210APending Publication Date: 2025-01-28CANON KK
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410979681.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-26
Filing Date
2024-07-22
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

While improving the thermal conductivity, the existing fixing members are difficult to maintain low hardness, resulting in possible breakage or plastic deformation during long-term use.

Method used

By reducing the cross -linking of silicon rubber in the elastic layer, the stretching mold is prepared to be less than 0.20MPa, the compressed modulus is 0.19 ~ 0.57MPa, and the initial hardness is reduced in advance in a high temperature environment to ensure the interchange The hardness is stable after the combination restructuring.

Benefits of technology

While maintaining a high thermal conduction rate, ensure the low hardness and durability of the fixed shadow component, and avoid the break or plastic deformation of the elastic layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119376210A_ABST
    Figure CN119376210A_ABST
Patent Text Reader

Abstract

The invention relates to an electrophotographic member, a thermal fixing apparatus, and an electrophotographic image forming apparatus. The electrophotographic member includes a substrate and an elastic layer on an outer peripheral surface of the substrate; wherein the elastic layer has a silicone rubber, the tensile modulus of the elastic layer in the direction perpendicular to the thickness direction thereof is 0.20 MPa or less, the compression modulus of the elastic layer in the thickness direction is 0.19-0.57 MPa, and the ratio (tensile modulus / compression modulus) of the tensile modulus of the elastic layer in the direction perpendicular to the thickness direction to the compression modulus of the elastic layer in the thickness direction is 0.80 or less. And the reduction rate of the compression modulus of each sample of the elastic layer in the direction corresponding to the thickness direction of the elastic layer is 5% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an electrophotographic member used in an electrophotographic image forming apparatus such as a copying machine or a printer, and a heat fixing apparatus and an electrophotographic image forming apparatus provided with the electrophotographic member. Background Art

[0002] In a thermal fixing device of an electrophotographic image forming device, a crimping portion is formed by a heating member and a pressing member arranged opposite to the heating member. When a recording material (paper, etc.) holding an unfixed colorant image is introduced into the crimping portion, the unfixed colorant becomes heated and pressurized, whereby the colorant melts and the image becomes fixed to the recording material. The heating member is a member that contacts the unfixed colorant image on the recording material, and the pressing member is a member arranged opposite to the heating member. A fixing member according to the present disclosure includes a heating member and a pressing member. The fixing member may have a rotatable shape, such as a roller shape or an endless belt shape. Such a fixing member includes a member having an elastic layer containing a rubber such as a cross-linked silicone rubber and a filler on a substrate formed of a metal or a heat-resistant resin.

[0003] As a purpose of achieving higher printing speed and improving image quality, recent years have witnessed a demand for further improvement in the thermal conductivity of the elastic layer of a fixing member in the thickness direction. Japanese Patent Application Publication No. 2005-300591 discloses a fixing member in which a thermally conductive filler contained in the elastic layer is formulated in a blend of a large particle size filler and a small particle size filler, thereby improving the thermal conductivity while suppressing an increase in the hardness of the elastic layer.

[0004] Japanese Patent Application Publication No. 2019-215531 discloses a fixing member, in which a heat conduction path is formed by arranging small particle fillers existing between large particle filler particles in the thickness direction of an elastic layer, while limiting the arrangement of the large particle filler particles in the thickness direction of the elastic layer, thereby resulting in increasing the thermal conductivity of the elastic layer in the thickness direction while limiting the content of the thermally conductive filler. Summary of the invention

[0005] The inventors have studied and found that, according to the fixing member of Japanese Patent Application Publication No. 2005-300591, when the thermal conductivity in the thickness direction of the elastic layer exceeds 1.5 W / (m·K), the filler compounding amount relative to the silicone rubber is required to be 60 vol% or more. Therefore, it is considered that the invention of Japanese Patent Application Publication No. 2005-300591 is difficult to provide a fixing member that exhibits higher thermal conductivity while suppressing an increase in hardness.

[0006] According to the fixing member of Japanese Patent Application Publication No. 2019-215531, while suppressing the increase in the hardness of the elastic layer, the thermal conductivity in the thickness direction is further improved. In order to further reduce the hardness of the elastic layer of the fixing member according to Japanese Patent Application Publication No. 2019-215531, the inventors produced and evaluated a fixing member in which the crosslinking degree of silicone rubber in the elastic layer was reduced. Specifically, the inventors studied a fixing member having a soft compression modulus of 0.19 to 0.57 MPa in the thickness direction of the elastic layer. As a result, the inventors found that when the fixing member according to the above study is used for a long time to form an electrophotographic image, the elastic layer may break or undergo plastic deformation.

[0007] At least one aspect of the present disclosure is directed to providing a fixing member having low hardness and excellent durability. At least one aspect of the present disclosure is directed to providing a heat fixing device that helps to stably form high-quality electrophotographic images. In addition, at least one aspect of the present disclosure is directed to providing an electrophotographic image forming device that stably forms high-quality electrophotographic images.

[0008] According to at least one aspect of the present disclosure, there is provided an electrophotographic member comprising:

[0009] matrix, and

[0010] An elastic layer on the outer peripheral surface of the substrate; wherein

[0011] The elastic layer comprises silicone rubber,

[0012] The elastic layer has a tensile modulus of 0.20 MPa or less in a direction perpendicular to its thickness direction.

[0013] The compression modulus of the elastic layer in the thickness direction is 0.19 to 0.57 MPa.

[0014] The ratio of the tensile modulus of the elastic layer in the direction perpendicular to the thickness direction to the compressive modulus of the elastic layer in the thickness direction (tensile modulus / compressive modulus) is 0.80 or less,

[0015] When the compression moduli H0 to H100 are taken as respective values ​​of the compression modulus in a direction corresponding to the thickness direction of the elastic layer in an atmosphere at a temperature of 240° C. and an oxygen concentration of 1% or less, every 10 hours up to 100 hours, and the reduction rate of each of the compression moduli H10 to H100 with respect to the compression modulus H0 serving as a reference is 5% or less.

[0016] According to at least one aspect of the present disclosure, a fixing member having low hardness and excellent durability is provided. According to at least one aspect of the present disclosure, a heat fixing device that helps to stably form high-quality electrophotographic images is provided. According to at least one aspect of the present disclosure, an electrophotographic image forming device capable of stably forming high-quality electrophotographic images is provided.

[0017] Further features of the present invention will become apparent from the following description of exemplary embodiments with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is an arrangement of a thermally conductive filler in an elastic layer of a fixing member according to an aspect of the present disclosure;

[0019] Figure 2A is a schematic cross-sectional view of a fixing belt;

[0020] Figure 2B is a schematic cross-sectional view of a fixing roller;

[0021] Figure 3A is a top view of a corona charging device;

[0022] Figure 3B is a cross-sectional view of a corona charging device;

[0023] Figure 4A and Figure 4B are diagrams showing a first cross section and a second cross section of an elastic layer of a fixing member in the form of a belt;

[0024] FIG. 5A to FIG. 5F is a schematic diagram showing a method for determining the degree and angle of arrangement of fillers in an elastic layer;

[0025] Fig. 6A and Figure 6B is an explanatory diagram of a method for measuring the tensile modulus of an elastic layer according to the present disclosure;

[0026] Figure 7 is a schematic cross-sectional view of an example of a heat fixing device of a heating belt and pressure belt type;

[0027] Figure 8 is a schematic cross-sectional view of an example of a heat fixing device of a heating belt pressure roller type; and

[0028] Fig. 9 is a schematic diagram of an example of the step of covering the surface layer. DETAILED DESCRIPTION

[0029] In the present disclosure, unless otherwise specified, "XX or more and YY or less" or "XX to YY" indicating a numerical range refers to a numerical range including the lower limit and the upper limit as endpoints. When the numerical range is stated in sections, the upper limit and the lower limit of each numerical range can be arbitrarily combined. In addition, in the present disclosure, expressions such as "at least one selected from the group consisting of XX, YY, and ZZ" refer to: XX; YY; ZZ; a combination of XX and YY; a combination of XX and ZZ; a combination of YY and ZZ; or a combination of XX, YY, and ZZ.

[0030] The reference numerals in the various drawings are as follows.

[0031] 1: core, 2: corona charging device, 3: substrate, 4: elastic layer, 5: adhesive layer, 6: surface layer, 7: large particle filler, 8: small particle filler, 100: fixing member, 201: front block, 202: rear block, 203: baffle, 204: baffle, 205: discharge wire, 206: grid, 401: sample, 401-1: first section, 401-2: second section, 11: fixing belt, 12: pressure belt, 13: induction heating member, 13a: induction coil, 13b: excitation core, 13c: coil holder, 14: excitation circuit, 15: temperature : temperature detecting element, 16: control circuit unit, 17: roller, 18: heating side roller, 19: tension roller, 20: pressing side roller, 21: fixing pad, 22: pressing pad, 23: sliding sheet, 24: sliding sheet, 25: separation member, 30: belt guide, 31: ceramic heater, 31a: heater substrate, 31b: heating layer, 31c: protective layer, 31d: sliding member, 32: stay, 33: pressing roller, 33a: metal core, 33b: elastic layer, 34: temperature detecting element, N: fixing roller gap, t: toner image, S: recording medium, M: motor.

[0032] The elastic layer according to Japanese Patent Application Publication No. 2019-215531 has a thermally conductive filler in the elastic layer, which is set to present a specific arrangement state in the thickness direction of the elastic layer, thereby further improving the thermal conductivity while suppressing the increase in the hardness of the elastic layer.

[0033] However, the results of the research conducted by the present inventors have shown that arranging the thermally conductive filler in the thickness direction of the elastic layer can result in a higher compression hardness of the elastic layer in the thickness direction than before the thermally conductive filler is arranged. This is conceivably because the above causes an effect of suppressing deformation in the case where the thermally conductive path within the filler as a rigid body is similar to a tie rod. Relying on the technology disclosed in Japanese Patent Application Publication No. 2019-215531, in order to obtain an elastic layer with still lower hardness, it is effective to reduce the tensile modulus of the silicone rubber in the elastic layer to, for example, 0.20 MPa or less.

[0034] However, in a fixing member in which the tensile modulus of the silicone rubber in the elastic layer is 0.20 MPa or less, the elastic layer may break or may suffer plastic deformation when used for a long time to form an electrophotographic image. The inventors speculate that the root cause of such breakage and plastic deformation is as follows. The cross-linked structure of the silicone rubber in the elastic layer decomposes over time, which leads to the so-called aging phenomenon, whereby the rubber elasticity gradually decreases. The elastic layer is usually constructed by adjusting the H / Vi of the addition-curing liquid silicone rubber used to form the elastic layer to allow the residual unsaturated aliphatic groups to remain in the cured silicone rubber, thereby resulting in the cross-linked structure being reconstructed by the reaction of these unsaturated aliphatic groups.

[0035] However, it takes longer to reconstruct the cross-linked structure than to cut the cross-linked structure. Therefore, when the elastic layer is set in a high temperature environment, in particular, the hardness is first reduced due to the cutting of the cross-linked structure of the silicone rubber, and then the cross-linked structure is reconstructed, whereby the hardness that was once reduced increases again. The phenomenon of reduced hardness before the reconstruction of the cross-linked structure is also referred to as "initial decrease in hardness" hereinafter. In the case where the hardness of the elastic layer is already low before being exposed to a high temperature environment, the hardness of the elastic layer is further reduced due to the initial decrease in the hardness of the elastic layer. It is believed that the elastic layer with a further decrease in hardness cannot withstand the repeated compression acting on it during the fixing process, and thus breaks or plastically deforms.

[0036] Therefore, the present inventors diligently studied how to obtain a fixing member that does not cause cracking or plastic deformation of the elastic layer with use even when the hardness of the silicone rubber in the elastic layer is further reduced. As a result, the present inventors found that by subjecting the elastic layer in which the hardness of the silicone rubber has been reduced to an initial hardness reduction treatment in advance, so that the elastic layer is used after the silicone rubber in the elastic layer has been switched from a treatment in which cleavage of the crosslinked structure of the silicone rubber predominates to a treatment in which reconstruction of the crosslinked structure predominates, it is possible to realize an elastic layer that, although flexible, does not break or suffer plastic deformation even when an electrophotographic image is repeatedly formed.

[0037] Such an elastic layer can be realized by the following feature, wherein, taking the compression moduli H0 to H100 as respective values ​​of the compression moduli in a direction corresponding to the thickness direction of the elastic layer in an atmosphere at a temperature of 240° C. and an oxygen concentration of 1 vol % or less, every 10 hours up to 100 hours, a decrease rate of each of the compression moduli H0 to H100 with respect to the compression modulus H0 serving as a reference is 5% or less.

[0038] That is, in the heat fixing step, in an environment where the silicone rubber in the elastic layer of the fixing member is exposed (a high temperature environment of 240° C., where the supply of oxygen is almost cut off), when the compression modulus of the elastic layer is measured every 10 hours up to 100 hours, the elastic layer that has undergone the initial hardness reduction step has a very small change rate in the compression modulus between consecutive hours. Specifically, the change rate is 5% or less.

[0039] A fixing member according to one aspect of the present disclosure has a substrate and an elastic layer on the outer peripheral surface of the substrate, wherein the elastic layer contains silicone rubber, the elastic layer has a tensile modulus of 0.20 MPa or less in a direction perpendicular to the thickness direction, and a compression modulus of 0.19 to 0.57 MPa in the thickness direction.

[0040] The ratio of the tensile modulus of the elastic layer in a direction perpendicular to the thickness direction to the compressive modulus of the elastic layer in the thickness direction (tensile modulus / compressive modulus) is 0.80 or less.

[0041] When the compression moduli H0 to H100 are respective values ​​of the compression modulus in a direction corresponding to the thickness direction of the elastic layer in an atmosphere at a temperature of 240° C. and an oxygen concentration of 1 vol % or less and taken from the elastic layer and are taken every 10 hours up to 100 hours, the reduction rate of each of the compression moduli H10 to H100 with respect to the compression modulus H0 serving as a reference is 5% or less.

[0042] The fact that the tensile modulus of the elastic layer in the direction perpendicular to the thickness direction is 0.20 MPa or less indicates that the silicone rubber sandwiched between the thermally conductive filler particles in the elastic layer has a low hardness.

[0043] The fact that the compression modulus of the elastic layer in the thickness direction is 0.19 to 0.57 MPa indicates that the elastic layer as a whole is flexible despite the fact that the thermally conductive filler is arranged in the thickness direction in the elastic layer. This provision means that sufficient flexibility is maintained even when the elastic layer is compressed by inserting silicone rubber between the thermally conductive filler particles arranged in the thickness direction of the elastic layer.

[0044] The ratio of the tensile modulus of the elastic layer in the direction perpendicular to the thickness direction to the compressive modulus of the elastic layer in the thickness direction (tensile modulus / compressive modulus) is 0.80 or less, indicating that the thermally conductive filler in the elastic layer is arranged in the thickness direction of the elastic layer.

[0045] The fact that, in the case where the compression moduli H0 to H100 are respective values ​​of the compression moduli in a direction corresponding to the thickness direction of the elastic layer in an atmosphere at a temperature of 240° C. and an oxygen concentration of 1 vol % or less, every 10 hours up to 100 hours as a rectangular parallelepiped sample of 50 mm in length, 50 mm in width and 150 μm in thickness sampled from the elastic layer, the reduction rate of each of the compression moduli H10 to H100 with respect to the compression modulus H0 as a reference is 5% or less, indicates that the cross-linked structure of the silicone rubber in the elastic layer has undergone an initial decrease in hardness, as described above.

[0046] The electrophotographic member according to an embodiment of the present disclosure will be explained in detail below based on a specific configuration.

[0047] (1) Overview of the structure of the electrophotographic member

[0048] The electrophotographic member in at least one aspect of the present disclosure is, for example, a fixing member. The electrophotographic member may be a pressure member such as a pressure belt or a pressure roller. The above will be explained in detail with reference to the drawings.

[0049] Figure 2A and Figure 2B is a schematic cross-sectional view showing a fixing member according to the present embodiment. Figure 2A An example of a fixing member in the form of a belt is shown, and Figure 2B An example of a fixing member in the form of a roller is shown. Figure 2A and Figure 2B In the figure, reference numeral 3 denotes a substrate, and reference numeral 4 denotes an elastic layer that includes silicone rubber and covers the outer peripheral surface of the substrate 3. Figure 2A and Figure 2B , the radial direction is the thickness direction of the elastic layer.

[0050] As described above, the fixing member according to the present embodiment includes a base 3 and an elastic layer 4 containing silicone rubber on the base 3. As shown in the figure, the fixing member may have a surface layer 6 on the elastic layer 4 containing silicone rubber. An adhesive layer 5 may be provided between the elastic layer 4 containing silicone rubber and the surface layer 6; in this case, the surface layer 6 is fixed to the outer peripheral surface of the elastic layer 4 containing silicone rubber via the adhesive layer 5. Figure 2A and Figure 2B The fixing members shown are all in an endless shape. An endless shape refers to a shape in which the same portion repeatedly (endlessly) passes through the fixing nip portion as a result of rotational motion in the circumferential direction.

[0051] (2) Matrix

[0052] In the fixing member Figure 2AIn the case of the belt-shaped substrate shown, the substrate 3 may use a metal such as an electroformed nickel sleeve or a stainless steel sleeve, or a heat-resistant resin such as polyimide. In particular, in the case where the heat fixing device relies on an electromagnetic induction heating scheme, an alloy containing nickel or iron as a main component is used from the viewpoint of heating efficiency. A layer for improving adhesion to the elastic layer may be provided on the outer surface (the surface on the elastic layer side) of the substrate 3. That is, the elastic layer 4 may be provided on the outer peripheral surface side of the substrate 3, but other layers may also be provided between the elastic layer 4 and the substrate 3. A layer imparting functions such as wear resistance and lubricity may also be provided on the inner surface (the surface on the opposite side to the outer surface) of the substrate 3. In the case where the substrate 3 is in the shape of a belt, the core is inserted into the sleeve during the production process described later.

[0053] In the fixing member, Figure 2B In the case of the roller form shown, a metal core composed of a metal or alloy such as aluminum or iron can be used for the base 3 as long as the metal core has sufficient strength to withstand the heat and pressure in the heat fixing device. Figure 2B In the embodiment, a solid metal core is used as the base 3; however, the base 3 may be a hollow metal core and may have a heat source such as a halogen lamp inside it.

[0054] (3-1) Elastic layer

[0055] The elastic layer is a layer that imparts flexibility to the electrophotographic member in order to ensure the fixing roller gap in the heat fixing device. In the case where the electrophotographic member is used as a heating member in contact with the toner on the paper, the elastic layer also serves as a layer that imparts flexibility to the surface of the member so that the surface can conform to the unevenness of the paper. The elastic layer includes rubber as a matrix and a thermally conductive filler dispersed in the rubber. More specifically, for example, the elastic layer contains silicone rubber and a thermally conductive filler, and is composed of a cured product obtained by curing a composition (hereinafter referred to as a silicone rubber composition) containing at least a starting material (such as a base polymer and a crosslinking agent) of silicone rubber and a thermally conductive filler.

[0056] When the silicone rubber composition is liquid, it is preferred that the thermally conductive filler is easily dispersed, because in this case, the elasticity of the elastic layer to be produced can be easily adjusted by adjusting the crosslinking degree of the thermally conductive filler according to the type and amount of the thermally conductive filler. In addition, the silicone rubber is preferably electrically insulating or semiconductive in order to impart orientation to the filler by surface charging before curing the electric field orientation rubber described below; for example, a cured silicone polymer can be used, as described below.

[0057] The base has a function of inducing elasticity in the elastic layer. From the viewpoint of bringing out the above-mentioned functionality of the elastic layer, the base of the elastic layer according to the present embodiment contains silicone rubber. Silicone rubber is preferred here because it exhibits high heat resistance that allows flexibility to be maintained even in an environment where the rubber reaches a high temperature of about 240° C. in a non-paper passing area. For example, a cured product of the following addition curing type silicone rubber composition can be used as the silicone rubber.

[0058] The silicone rubber mixture generally comprises at least the following components (a) to (c), and contains the following component (d) as a given component:

[0059] Component (a): a linear organopolysiloxane having an unsaturated aliphatic group;

[0060] Component (b): an organopolysiloxane having silicon-bonded active hydrogen;

[0061] Component (c): a catalyst; and

[0062] Component (d): thermally conductive filler.

[0063] Hereinafter, each component will be described.

[0064] Component (a): Straight chain organopolysiloxane having unsaturated aliphatic groups

[0065] The linear organopolysiloxane having an unsaturated aliphatic group is an organopolysiloxane having an unsaturated aliphatic group such as a vinyl group and having a linear structure of a siloxane bond. Examples thereof include at least one selected from the group consisting of compounds represented by the following formulae (1) and (2).

[0066]

[0067] In formula (1), m 1 represents an integer greater than or equal to 0 (preferably 500 to 1100), n 1 represents an integer of 3 or more (preferably 10 to 40). In formula (1), each R 1 independently represent a monovalent unsubstituted or substituted hydrocarbon group containing no unsaturated aliphatic groups, provided that at least one R 1 represents a methyl group, and each R 2 independently represents an unsaturated aliphatic group.

[0068]

[0069] In formula (2), n 2 represents an integer greater than 1 (preferably 500 to 1100), each R 3independently represent a monovalent unsubstituted or substituted hydrocarbon group containing no unsaturated aliphatic groups, provided that at least one R 3 represents a methyl group, and each R 4 independently represents an unsaturated aliphatic group.

[0070] In formulas (1) and (2), R 1 and R 3 Examples of the monovalent unsubstituted or substituted hydrocarbon group containing no unsaturated aliphatic group represented by include the following groups.

[0071] -Unsubstituted hydrocarbon

[0072] Alkyl (eg, methyl, ethyl, propyl, butyl, pentyl, and hexyl).

[0073] Aryl (eg, phenyl).

[0074] -Substituted hydrocarbon

[0075] Substituted alkyl (eg, chloromethyl, 3-chloropropyl, 3,3,3-trifluoropropyl, 3-cyanopropyl, and 3-methoxypropyl).

[0076] The organopolysiloxane represented by formula (1) and (2) has at least one methyl group directly bonded to the silicon atom forming the chain structure. 1 and R 3 More than 50% of each is preferably methyl, and more preferably all R 1 and R 3 They are all methyl.

[0077] In addition, R in formula (1) and (2) can be 2 and R 4 Examples of unsaturated aliphatic groups represented by include the following groups. Examples of unsaturated aliphatic groups include vinyl, allyl, 3-butenyl, 4-pentenyl and 5-hexenyl. In these groups, R 2 and R 4 Vinyl groups are preferred because they are easy to synthesize and handle, have low costs, and can easily undergo cross-linking reactions.

[0078] From the viewpoint of moldability, the viscosity of component (a) is preferably 1000 mm 2 / s~20000mm 2 / s, more preferably 3000mm 2 / s~8000mm 2 / s. When the above viscosity is 1000mm 2 / s or more, the elastic layer can be adjusted to the required hardness, and when the viscosity is 20000mm 2When the viscosity is 0.17V or less, the filler is easily oriented by the electric field. The viscosity (kinematic viscosity) can be measured according to JIS Z8803:2011 using, for example, a capillary viscometer or a rotational viscometer.

[0079] The blending amount of the component (a) is preferably 55 vol% or more based on the silicone rubber composition for forming the elastic layer from the viewpoint of durability, and is preferably 65 vol% or less from the viewpoint of thermal conductivity.

[0080] Component (b): an organopolysiloxane having silicon-bonded active hydrogen

[0081] The organopolysiloxane having silicon-bonded active hydrogen, which reacts with the unsaturated aliphatic groups of component (a) under the action of a catalyst, serves as a crosslinking agent for forming the cured silicone rubber.

[0082] Any organopolysiloxane having Si-H bonds can be used as the component (b). In particular, an organopolysiloxane having an average silicon-bonded hydrogen atom number of 3 or more per molecule is preferably used from the viewpoint of reactivity with the unsaturated aliphatic group of the component (a).

[0083] Specific examples of component (b) include linear organopolysiloxanes represented by the following formula (3) and cyclic organopolysiloxanes represented by the following formula (4).

[0084]

[0085] In formula (3), m 2 represents an integer greater than or equal to 0 (preferably 10 to 30), n 3 represents an integer of 3 or more (preferably 5 to 20), R 5 Each independently represents a monovalent unsubstituted or substituted hydrocarbon group containing no unsaturated aliphatic group.

[0086]

[0087] In formula (4), m 3 represents an integer greater than or equal to 0 (preferably 10 to 30), n 4 represents an integer of 3 or more (preferably 5 to 20), and R 6 Each independently represents a monovalent unsubstituted or substituted hydrocarbon group containing no unsaturated aliphatic group.

[0088] It can be obtained from R in formula (3) and formula (4) 5 and R 6 Examples of the monovalent unsubstituted or substituted hydrocarbon group containing no unsaturated aliphatic group represented by 1 The same groups as those mentioned above. Among them, preferably R 5 and R 6More than 50% of each are methyl groups, and more preferably all R 5 and R 6 All are methyl groups because synthesis and handling are easy and excellent heat resistance is easily obtained.

[0089] Component (c): Catalyst

[0090] Examples of catalysts for forming silicone rubber include hydrosilylation catalysts for accelerating the curing reaction. Known substances such as platinum compounds and rhodium compounds can be used as hydrosilylation catalysts. The amount of the catalyst can be appropriately set without particular limitation.

[0091] Component (d): Thermally conductive filler

[0092] The thermal conductive filler is selected in consideration of the thermal conductivity, specific heat capacity, density, particle size, relative dielectric constant, etc. of the filler itself. In order to improve the heat transfer characteristics, the following thermal conductive fillers such as inorganic materials, especially metals, metal compounds, etc. can be used as the thermal conductive filler. Silicon carbide, silicon nitride, boron nitride, aluminum nitride, aluminum oxide, zinc oxide, magnesium oxide, silicon dioxide, copper, aluminum, silver, iron, nickel, metal silicon and carbon fiber.

[0093] From the viewpoint of the thermal conductivity, resistance value and relative dielectric constant of the filler itself, it is more preferable to use at least one filler selected from the group consisting of aluminum oxide, zinc oxide, metal silicon, silicon carbide, boron nitride and magnesium oxide. From the viewpoint of the heat resistance of the elastic layer, it is more preferable to use a filler containing less ionic impurities (such as Na + ) are more preferably metallic silicon, silicon carbide, etc. in this article.

[0094] From the viewpoint of affinity with silicone and in consideration of resistance value, the filler may be subjected to surface treatment. Specifically, fillers such as aluminum oxide, silicon dioxide or magnesium oxide having active groups such as hydroxyl groups on the surface may be surface treated, for example, with a silane coupling agent and hexamethyldisilazane. Metal fillers may be surface treated by forming an oxide film.

[0095] Furthermore, the resistance value can be adjusted in the entire silicone rubber composition. Even in the case of a filler having a relatively low resistance value, the resistance value of the entire composition can be adjusted by simultaneously using a second filler having a high resistance value.

[0096] The particle size of the filler is preferably 0.1 μm to 100 μm, more preferably 0.3 μm to 30 μm. The term particle size herein refers to the volume average particle size.

[0097] From the viewpoint of reducing the hardness, the filler content in the elastic layer is preferably 30 vol% to less than 50 vol%, and more preferably 35 vol% to 40 vol%, relative to the silicone rubber.

[0098] (3-2) Orientation of the Thermally Conductive Filler in the Elastic Layer

[0099] The thermally conductive filler may be oriented / aligned in the electric field applying step described below.

[0100] It is preferable to avoid arranging large particle fillers having a circle equivalent diameter of 5 μm or more (e.g., 5 to 30 μm) as much as possible. In the case of a binary image with a size of 150 μm×100 μm obtained at any 5 locations in the first cross section in the thickness direction and the circumferential direction (thickness-circumferential direction) of the elastic layer, and in the case of a binary image with a size of 150 μm×100 μm obtained at any 5 locations in the second cross section in the thickness direction and the axial direction (thickness-axial direction) of the elastic layer, the average value of each area ratio (%) of the large particle fillers in a total of 10 binary images (hereinafter also referred to as "the average area ratio of the large particle fillers") is preferably 20% to 40%. The area ratio of the large particle fillers is represented here by [(the total surface area of ​​the large particle fillers in the binary image×100) / (the surface area of ​​the binary image)]. When the average area ratio of the large-particle filler is 20% or more, the distance between the large-particle filler particles becomes shorter, so that when a sufficiently strong local electric field is applied, a sufficiently large local electric field can be generated, and the small-particle filler particles existing between the large-particle filler particles can be easily arranged in a sufficient manner. When the average area ratio of the large-particle filler is 40% or less, the hardness of the elastic layer can be easily reduced in a sufficient manner.

[0101] Preferably, small particle fillers having an equivalent circle diameter of less than 5 μm are arranged. The average value of the area ratio of the small particle filler in the binary image (hereinafter also referred to as the "average area ratio of the small particle filler") is preferably in the range of 10% to 20%. The area ratio of the small particle filler herein represents [(the sum of the surface areas of the small particle filler particles in the binary image × 100) / (the surface area of ​​the binary image)]. In the case where the average area ratio of the small particle filler is lower than 10%, it is difficult to arrange the small particle filler and it is difficult to sufficiently improve the thermal conductivity. In the case where the average area ratio of the small particle filler is higher than 20%, the viscosity of the material may increase, and problems may arise in the processability and smoothness of the elastic layer.

[0102] The sum of the average area ratio of the large particle filler and the average area ratio of the small particle filler is preferably 30% to 60%, and particularly preferably 30% to 50%. The sum of the average area ratio of the large particle filler and the average area ratio of the small particle filler is a value closely related to the overall volume ratio of the filler in the elastic layer. By setting the sum of the average area ratio of the large particle filler and the average area ratio of the small particle filler within the above range, a higher thermal conductivity and a suppressed increase in hardness can be better combined in the elastic layer.

[0103] (3-3) Determining the arrangement state of the thermally conductive filler in the elastic layer

[0104] The arrangement state of the thermally conductive filler can be determined by deriving a two-dimensional Fourier transform using a binarized image obtained from a cross-sectional image of the elastic layer. Specific procedures include the following.

[0105] First, prepare a measurement sample. For example, in the case where the fixing member is Figure 4A In the case of the fixing belt 400 shown in FIG. Figure 4B As shown, 10 samples 401 with a length of 5 mm, a width of 5 mm, and a thickness equal to the total thickness of the fixing belt are taken at 10 arbitrary positions of the fixing belt. Then, for 5 of the 10 samples obtained above, the cross-section in the circumferential direction of the fixing belt, that is, the cross-section including the first cross-section 401-1 of the elastic layer in the thickness-circumferential direction, is polished by ion beam. For the remaining 5 samples, the cross-section in the direction perpendicular to the circumferential direction of the fixing belt is polished by ion beam, that is, the cross-section including the second cross-section 401-2 of the elastic layer in the thickness-axial direction. The cross-section is polished by ion beam using a cross-section polisher. The cross-section polishing by ion beam prevents the filler from falling off the sample, prevents the abrasive from mixing into the sample, and forms a cross-section showing few polishing marks.

[0106] For the five samples in which the first cross section of the elastic layer was polished and the five samples in which the second cross section of the elastic layer was polished, the first cross section of the elastic layer and the second cross section of the elastic layer were observed under a laser microscope or a scanning electron microscope (SEM) to obtain respective cross-sectional images in an area of ​​150 μm×100 μm ( Figure 5A ).

[0107] Each obtained image was converted to black and white using commercially available image software, so that the filler part appeared white and the silicone rubber part appeared black ( Figure 5B ). Using Otsu's method as the binarization method.

[0108] The circle equivalent diameters of the filler particles 7 and 8 in the binary image are calculated, and the image is segmented into an image where only the large particle filler 7 with a circle equivalent diameter of 5 μm or more remains ( Figure 5C ) and only the image of small particle filler 8 with a circle equivalent diameter less than 5 μm remains ( Figure 5D ). The area ratio of the large particle filler 7 and the small particle filler 8 (the ratio of the total area of ​​each filler 7 or 8 to the total area of ​​the image) is calculated from each image. The circle equivalent diameter of each filler refers to the diameter of a circle having the same surface area as the filler.

[0109] By performing a two-dimensional Fourier transform analysis on the large particle packing image and the small particle packing image, individual ellipse diagrams depicting the direction and degree of packing arrangement are obtained ( Figure 5E and Fig. 5F ). The two-dimensional Fourier transform itself has a peak in a direction orthogonal to the periodicity of the binarized image, so the ellipse diagram is generated by a 90° phase shift of the result of the two-dimensional Fourier transform. From the angle formed by the major axis of the ellipse in each ellipse diagram, the arrangement angle Φ and the packing arrangement degree f defined as f=1-(y / x) are calculated, where x is the major axis of the ellipse and y is the minor axis of the ellipse.

[0110] The arrangement angle Φ indicates the arrangement direction of the packing; Figure 5E and Fig. 5F In the diagram, the 90°-270° direction indicates the thickness direction of the elastic layer, and the 0°-180° direction indicates the circumferential direction or axial direction of the elastic layer. Therefore, the closer the arrangement angle Φ is to 90°, the greater the degree of arrangement of the filler in the thickness direction.

[0111] The degree of arrangement f represents the flattening rate of the ellipse, and takes a value from 0 to less than 1. When f is 0, the ellipse is a circle, indicating a completely random state without arrangement; as f approaches 1, the flattening rate of the ellipse becomes larger, and the degree of arrangement of the packing becomes larger.

[0112] The filler arrangement angle Φ and arrangement degree f were calculated as average values ​​of values ​​at a total of 10 positions, namely, 5 positions of the first cross section in the thickness-circumferential direction of the elastic layer and 5 positions in the thickness-axial direction of the elastic layer.

[0113] In this embodiment, the average area ratio of the large particle filler having a filler particle size (equivalent circle diameter) of 5 μm or more is preferably 20% to 40%, and more preferably 30% to 35%. When the average area ratio of the large particle filler is 20% or more, the inter-particle distance between the large particle filler particles becomes short, and a local electric field can be easily generated in a simple manner. Therefore, the small particle filler particles existing between the large particle filler particles can be fully arranged, so that a higher thermal conductivity can be more easily achieved. When the average area ratio of the large particle filler is 40% or less, the hardness of the elastic layer can be easily reduced in a sufficient manner.

[0114] Here, fL, which is the average degree of arrangement of the large particle filler, is preferably in the range of 0.00 to 0.15, and more preferably 0.10 to 0.15. When fL is 0.15 or less, low hardness of the elastic layer can be achieved.

[0115] In addition, ΦL, which is the average arrangement angle of the large particle filler, can take any value from 0° to 180°.

[0116] The average area ratio of the small particle filler with a particle size of less than 5 μm is preferably 10% to 20%, and more preferably 10% to 15%. When the average area ratio of the small particle filler is 10% or more, a sufficiently high thermal conductivity can be achieved. When the average area ratio of the small particle filler is 20% or less, problems with processability and smoothness caused by high material viscosity can be prevented.

[0117] The value of ΦS, which is the average arrangement angle of the small particle filler, is preferably 60° to 120°, and more preferably 80° to 100°. Assuming that the direction in which ΦS is 90° is the thickness direction of the elastic layer, the closer ΦS is to 90°, the greater the degree of arrangement in the thickness direction. Therefore, when ΦS is within the above range, the thermal conductivity in the thickness direction can be improved. Here, ΦS of 30° and 150° are synonymous with the heat transfer function in the thickness direction, because 30° and 150° show a mirror relationship relative to each other, with 90° as the boundary.

[0118] (3-4) Step of applying an electric field to the elastic layer

[0119] Next, an embodiment of the corona charging device 2 and the step of applying an electric field to the elastic layer using the corona charging device 2 is described. The corona charging scheme includes a scorotron scheme that relies on a grid electrode between the corona wire and the charged body, and a corotron scheme without a grid electrode; from the viewpoint of controllability of the surface potential of the charged body, the scorotron scheme is preferred here.

[0120] like Figure 3A and Figure 3B As shown, the corona charging device 2 includes a front block 201, a rear block 202, and baffles 203, 204. In addition, a discharge wire 205 spans between the front block 201 and the rear block 202, so that when a charging bias is applied thereto by a high voltage power source, the discharge wire 205 undergoes discharge, thereby charging the surface of the pre-cured elastic layer 4 on the substrate as a charged body.

[0121] In the same manner as the structure of a general corona charging device, a high voltage is applied to a discharge wire 205 as a discharge member. The ion flow obtained by discharging to the baffles 203 and 204 is controlled by applying a high voltage to the grid 206, thereby controlling the surface of the elastic layer 4 to a desired charged potential. At this time, the substrate 3 or the core 1 holding the substrate 3 is grounded (not shown), and therefore, by controlling the surface potential of the surface of the elastic layer 4, a desired electric field can be generated in the elastic layer 4.

[0122] In the detailed description of the method for producing the fixing member of the above embodiment, first, an elastic layer having silicone rubber containing a thermally conductive filler is formed on a substrate. Figure 3AAs shown, the corona charging device 2 is arranged close to and opposite to the elastic layer 4 along the width direction of the pre-cured elastic layer 4 of the fixing member 100. A voltage is applied to the grid 206 of the corona charging device 2, and in this state, the fixing member 100 is rotated at, for example, 141 rpm for 160 seconds to cause discharge, thereby charging the surface of the elastic layer. The distance between the surface of the elastic layer and the grid 206 can be set to 1 mm and 10 mm. Therefore, by charging the surface of the elastic layer 4, an electric field is generated in the elastic layer, so that the thermal conductive filler is oriented. Then, the elastic layer is cured, for example, by heating, to fix the orientation of the filler.

[0123] Preferably, from the viewpoint of causing effective electrostatic interaction with the filler, the voltage applied to the grid 206 is in the range of 0.1 kV to 3 kV as an absolute value (0.2 to 6 kV at Vp-p in the case of applying AC). In the case of bringing about the orientation of the filler in the thickness direction of the elastic layer by means of an electric field, it is important to generate an electric field in the thickness direction of the elastic layer 4. If the sign of the applied voltage is set to be equivalent to the sign of the voltage applied to the wire, the direction of the electric field is reversed regardless of whether the sign is negative or positive; however, the effect caused is the same. In the case of AC charging for the purpose of suppressing the flow of the liquid surface described later, the phases of the waveforms of the wire and the grid are preferably matched with each other. Depending on the type of thermally conductive filler, it may be difficult to impart orientation to an amorphous filler; in this case, it is preferable to increase the voltage applied to the grid 206. This ostensibly indicates the relationship between the dielectric constants of the silicone rubber component and the thermally conductive filler. In the case where the difference in dielectric constant between the silicone rubber and the filler is large, the orientation of the amorphous filler can be imparted with a relatively small applied voltage. On the other hand, when the voltage applied to the gate 206 is too large, the electrostatic repulsion from the surface charge of the elastic layer becomes large, causing the liquid surface flow and the deterioration of the surface characteristics of the elastic layer 4. Therefore, it is more preferable that the voltage applied to the gate 206 is in the range of 0.1 kV to 1.5 kV as an absolute value (1.2 to 3 kV at Vp-p in the case of applying AC). This liquid surface flow can be alleviated by AC charging.

[0124] As a configuration for controlling the potential of the elastic layer surface in the longitudinal direction, for example, Figure 3A The structure shown in , wherein the entire elastic layer 4 is charged by rotating the fixing belt 11 around its central axis, and a voltage is applied to the grid 206. From the viewpoint of stably imparting orientation to the filler, the rotation speed of the fixing belt is preferably 10 rpm to 500 rpm, and the treatment time is preferably 20 seconds or more. The orientation of the amorphous filler can be controlled by controlling the surface potential and the application time of the electric field.

[0125] In the corona charging device, a reciprocating vibration of about ±1 to 10 mm at a frequency of about 1 to 10 Hz is caused in the longitudinal direction of the fixing member by a reciprocating mechanism, as a result of which a sharp change in thermal conductivity, surface properties and hardness at the boundary portion between the area where the electric field is applied and the area where the electric field is not applied can be limited.

[0126] Stainless steel, nickel, molybdenum, tungsten, etc. can be used as the discharge wire 205, but tungsten, which boasts very high stability among metals, is preferably used herein. The discharge wire crossing the inner side of the baffle may have a circular cross-sectional shape or a sawtooth shape.

[0127] The diameter of the discharge wire 205 is preferably 40 μm to 100 μm. The fundamental reason is that by regulating the diameter of the discharge wire within such a range, the discharge wire can be prevented from being cut by ions during discharge, while eliminating the need for excessively high voltage required to trigger corona discharge. A DC voltage or an AC voltage can be used as the voltage applied to the discharge wire 205. In the case of an alternating voltage, the latter is preferably applied at a frequency of about 0.01 Hz to 1000 Hz. Voltage application can be achieved by using an arbitrary waveform generator to output, for example, a rectangular wave or a sine wave.

[0128] (3-5) Adjustment of elastic modulus of silicone rubber

[0129] In order to achieve high thermal conductivity in the elastic layer of the present disclosure, it is preferred that the filler is oriented / arranged in the thickness direction in the above process. When the filler is oriented / arranged, anisotropy with respect to the tensile modulus in the direction perpendicular to the thickness direction is generated in proportion to the increase in the compression modulus (hardness) in the thickness direction, compared with the case where the filler is not oriented.

[0130] By arranging the thermally conductive filler in the thickness direction of the elastic layer to improve the thermal conductivity of the elastic layer in the thickness direction, the ratio of the tensile modulus in the direction perpendicular to the thickness direction of the elastic layer to the compressive modulus in the thickness direction of the elastic layer (tensile modulus / compressive modulus) can be 0.80 or less. The lower limit of the above ratio is not particularly limited, and is, for example, 0.10 or more. The above ratio is preferably 0.10 to 0.55, and more preferably 0.10 to 0.40.

[0131] The fact that the "tensile modulus / compression modulus" of the elastic layer takes the above value indicates that anisotropy occurs between the compression modulus in the thickness direction and the tensile modulus in the direction perpendicular to the thickness direction. This can explain the fact that the compression modulus is relatively hard relative to the softness of the silicone rubber in the elastic layer due to the arrangement of the filler, and also explains the degree of arrangement of the filler in the entire elastic layer.

[0132] The above ratio can be adjusted, for example, by adjusting the cross-linking degree of the silicone rubber and / or by controlling the degree of arrangement of the filler in the above-mentioned electric field application step when the elastic layer is formed.

[0133] On the other hand, when the elastic modulus in the compression direction increases, the ability to conform to the unevenness of the paper fiber decreases. Therefore, in order to offset the increase in the elastic modulus, the elastic modulus (cross-linking degree) of the silicone rubber (polymer) excluding the filler is reduced, and the overall compression modulus of the elastic layer is set within the range of 0.19 to 0.57 MPa.

[0134] Here, the tensile modulus in the direction perpendicular to the thickness direction of the elastic layer is an indicator of the degree of crosslinking of the silicone rubber in the elastic layer, that is, the elastic modulus of the silicone rubber. Specifically, the compression modulus of the elastic layer is affected not only by the elastic modulus of the silicone rubber in the elastic layer, but also by the arrangement state of the thermally conductive filler. On the other hand, the tensile modulus of the elastic layer in the direction perpendicular to the thickness direction is determined by the silicone rubber in the elastic layer. In the elastic layer according to the present disclosure, the tensile modulus in the direction perpendicular to the thickness direction is 0.20 MPa or less, preferably 0.19 MPa or less, and more preferably 0.18 MPa or less. The lower limit is not particularly limited, and from the viewpoint of maintaining the strength of the elastic layer, it is preferably 0.01 MPa or more, and particularly preferably 0.10 MPa or more. The preferred range of the tensile modulus is 0.01 to 0.20 MPa, particularly 0.10 to 0.20 MPa, and further 0.10 to 0.19 MPa. By the fact that the tensile modulus of the elastic layer in the direction perpendicular to the thickness direction is 0.20 MPa or less, even when the thermally conductive filler in the elastic layer is arranged in the thickness direction, the compression modulus of the entire elastic layer can be set within the above-mentioned range of 0.19 to 0.57 MPa. For example, in the case where the electrophotographic member according to the present disclosure is an electrophotographic belt having an endless shape or an electrophotographic roller having a roller shape, the direction perpendicular to the thickness direction of the elastic layer ( Fig. 6A The arrow 603 in FIG. 6 may represent the circumferential direction of the electrophotographic belt or electrophotographic roller, or a direction perpendicular to the circumferential direction, that is, a direction along the rotation axis.

[0135] In order to make the tensile modulus in the direction perpendicular to the thickness direction of the elastic layer within the above range, it is effective to increase the molecular weight of component (a) to increase the distance between crosslinking points and / or adjust the addition amount of component (b) so that the crosslinking density is not excessively high.

[0136] Specifically, the molar ratio (H / Vi) of Si-H in component (b) to the unsaturated aliphatic group in component (a) is preferably 0.5 or less, and the toluene extraction rate is about 30 to 45%.

[0137] A rectangular parallelepiped sample of 50 mm in length, 50 mm in width, and 150 μm in thickness sampled from the elastic layer according to the present embodiment was placed in an atmosphere of an oxygen concentration of 1 vol% or less and a temperature of 240° C. for 100 hours. Considering H10 to H100 as the average value of the compression modulus of the sample in the thickness direction measured 3 times every 10 hours, the reduction rate of each of the compression moduli H10 to H100 relative to the compression modulus H0 at 0 hours as a reference is 5% or less. The fact that the reduction rate of each of H10 to H100 is 5% or less indicates that the elastic layer is not easily subjected to softening degradation over a long period of time in the overall durability.

[0138] The molecular weight Mw of the silicone rubber is preferably 60,000 to 100,000. When Mw is 60,000 or more, the elastic modulus is low, and when Mw is 100,000 or less, the polymer viscosity does not excessively rise during electric field orientation, so that the filler can be more easily oriented.

[0139] The swelling ratio in the toluene extraction test is a known method for indirectly measuring the crosslinking density of silicone rubber; here, the swelling ratio calculated according to the following formula is preferably 900% to 1200%.

[0140] Swelling ratio (%) = (Wtol-Wf) / (Wdry-Wf)

[0141] Wtol: The weight of the sample containing toluene after immersion in toluene

[0142] Wf: filler weight in the sample

[0143] Wdry: weight of sample after soaking in toluene and drying

[0144] When the swelling ratio is 900% or less, it is difficult to bring about an elastic modulus of 0.20 MPa or less, whereas when the swelling ratio is 1200% or more, excessive softness is required, which translates into impaired formability.

[0145] By adjusting the swelling ratio to be within the above range, the elastic layer can express low flexibility, that is, a tensile modulus of 0.20 MPa or less.

[0146] (3-6) Measures to address softening and degradation of the elastic layer

[0147] Among the overall durability, methods for slowing down the progress of softening degradation of the elastic layer over a long period of time include methods involving further subjecting the cured elastic layer to high temperature baking to promote the preliminary oxidation / condensation reaction of the methyl group and form a branched organopolysiloxane structure. Detailed description is given below.

[0148] Method for further subjecting the cured elastic layer to high temperature baking and promoting the pre-oxidation / condensation reaction of the methyl group to form a branched organopolysiloxane structure

[0149] The cured elastic layer is heated at a high temperature ranging from 280°C to 350°C, more preferably from 300°C to 350°C in an oxygen-free state, resulting in the following methyl group oxidation / condensation reaction as shown in reaction formula (5) and methyl group oxidation / cleavage reaction as shown in reaction formula (6). The heating time is, for example, 1 minute to 10 minutes.

[0150]

[0151] By heating the elastic layer at a high temperature in a low oxygen concentration state, a softening reaction caused by oxidation / cleavage of the methyl group and a curing reaction caused by oxidation / condensation proceed simultaneously in the elastic layer. It is considered that once the softening reaction and the curing reaction proceed to a given extent, the changed hardness stabilizes at the same hardness as before the high-temperature heating, and the elastic layer is less likely to undergo softening deterioration.

[0152] Once the above changes progress, a branched organosiloxane structure is formed, such as the structure given by reaction formula (5). The branched organosiloxane structure contains three Si-O bonds per Si atom, and its apparent bond energy is greater than the bond energy of the Si-C bond with the side chain methyl group or the Si-C-C and Si bonds of the crosslinking point; therefore, the branched organosiloxane structure is stable to thermal and mechanical loads.

[0153] The guiding principles for this state include: the ratio of the T unit (three O atoms bonded to one Si atom) of the siloxane bond in the silicone rubber to the D unit (two O atoms bonded to one Si atom) (T unit / D unit) is 0.030 or more; and when the silicone rubber is heated at 150°C for 1 hour, the total amount of hexamethylcyclotrisiloxane (D3), octamethylcyclotetrasiloxane (D4) and decamethylcyclopentasiloxane (D5) generated is 1.5 ppm or more. More preferably, any of the above items is met, because the change in hardness in subsequent use is small. The former indicates that the curing reaction of the silicone rubber has been completely carried out to stability, while the latter indicates that the softening reaction of the silicone rubber has been completely carried out to stability.

[0154] The ratio of the T unit to the D unit is preferably 0.030 to 0.100, more preferably 0.030 to 0.060.

[0155] The total amount of cyclic siloxanes D3 to D5 produced is preferably 1.5 to 10 ppm, more preferably 2.0 to 5.0 ppm.

[0156] The ratio of T units (three O atoms bonded to one Si atom) to D units (two O atoms bonded to one Si atom) of the siloxane bonds of silicone rubber in the elastic layer is dependent on NMR analysis ( 29The calculated results were obtained from Si-NMR (product name: JEOL JNM-ECA400; JEOL Resonance Co., Ltd.) The sample was separated from the elastic layer by inserting a blade near the interface between the base layer and the elastic layer and near the interface between the elastic layer and the surface layer of the fixing member.

[0157] The ratio of the integrated value of the peak corresponding to the T unit (55-60 ppm) to the integrated value of the peak corresponding to the D unit (-25 ppm) was quantified and calculated. The measurement was performed according to the DDMAS method with 1000 as the scan number.

[0158] The amount of cyclic siloxane generated when silicone rubber was heated at 150° C. for 1 hour was calculated by headspace gas chromatography-mass spectrometry (HS-GC / MS) based on the sum of the integrated values ​​of the retention times (RT) of the cyclic siloxanes D3, D4, and D5 relative to the measured integrated values ​​of toluene as a reference substance at a predetermined concentration. The measuring apparatus used was HS-GC / MS (product name: TurboMatrix HS40 Clarus 690GC; PerkinElmer Inc.), and the measuring conditions included HS temperature: 150° C. for 1 hour, GC: 40 to 300° C. (52 minutes), and MS: 35 to 500 Da.

[0159] (4) Adhesive layer of fixing member

[0160] like Figure 2A and Figure 2B As shown, the adhesive layer 5 is a layer formed by bonding the elastic layer 4 and the surface layer (peeling layer) 6 using, for example, an addition-curing silicone rubber adhesive. It is preferable to use an addition-curing silicone rubber containing a self-adhesive component as an adhesive. Specifically, the addition-curing silicone rubber contains an organopolysiloxane having a plurality of unsaturated aliphatic groups represented by vinyl groups in the molecular chain, a hydrogen organopolysiloxane, and a platinum compound as a crosslinking catalyst. The addition-curing silicone rubber is cured by an addition reaction. A known adhesive can be used as such an adhesive.

[0161] Examples of self-adhesive components include the following:

[0162] - silane having at least one, preferably two or more, functional groups selected from alkenyl groups such as vinyl groups, (meth)acryloyloxy groups, hydrosilyl groups (SiH groups), epoxy groups, alkoxysilyl groups, carbonyl groups and phenyl groups;

[0163] - organosilicon compounds, for example cyclic or linear siloxanes having 2 to 30 silicon atoms, preferably 4 to 20 silicon atoms;

[0164] - Non-silicon organic compounds (i.e. compounds without silicon atoms in the molecule) that may contain oxygen atoms in the molecule. However, one molecule of the organic compound contains 1 to 4 aromatic rings, preferably 1 to 2 aromatic rings such as phenylene structures, and the valence is 1 to 4, preferably 2 to 4. Each molecule of the organic compound contains at least one, preferably 2 to 4 functional groups (e.g. alkenyl, (meth)acryloyloxy) that can contribute to the hydrosilylation addition reaction.

[0165] The above-mentioned self-adhesive components may be used alone or in combination of two or more.

[0166] From the viewpoint of adjusting viscosity and ensuring heat resistance, filler components may be added to the adhesive within the scope consistent with the purpose of the present disclosure. Examples of such filler components include:

[0167] - Silica, alumina, iron oxide, titanium oxide, cerium oxide, cerium hydroxide and carbon black.

[0168] Such addition curing type silicone rubber adhesive is commercially available and can be easily obtained.

[0169] The thickness of the adhesive layer is preferably 20 μm or less. By setting the thickness of the adhesive layer to 20 μm or less, the thermal resistance of the fixing member can be reduced, and heat from the inner surface side (substrate side) can be efficiently transferred to the recording material (recording medium).

[0170] (5) Surface layer of fixing member

[0171] The surface layer 6 is composed of a fluororesin, and a tube method or a coating method is adopted as a forming method. The tube method involves coating a tubular formed product with a resin exemplified below.

[0172] - Tetrafluoroethylene-perfluoro(alkyl vinyl ether) copolymer (PFA), polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), etc. From the viewpoint of moldability and toner releasability, PFA is preferred among the above-exemplified resin materials.

[0173] The thickness of the fluororesin layer (surface layer) is preferably 10 μm to 50 μm. This is because when the fluororesin layer is laid, the elasticity of the underlying elastic layer can be maintained while ensuring wear resistance, and the surface hardness of the fixing member can be prevented from becoming too high.

[0174] The adhesiveness can be improved by previously subjecting the inner surface of the fluororesin tube to sodium treatment, excimer laser treatment, ammonia treatment, or the like.

[0175] Fig. 9Schematic diagram of an example of a step of laying a surface layer 6 on an elastic layer 4 containing silicone rubber via an addition-curing silicone rubber adhesive. The addition-curing silicone rubber adhesive 5 is applied to the surface of the elastic layer 4 formed on the outer peripheral surface of the base 3. Then, the outer surface is further coated (covered) with a fluororesin tube 6 as the surface layer 6.

[0176] The coating method of the fluororesin tube is not particularly limited, and a method involving coating an addition-curing silicone rubber adhesive as a lubricant or a method involving expanding a fluororesin tube from the outside and then coating the fluororesin tube may be used.

[0177] The excess addition curing silicone rubber adhesive 5 remaining between the elastic layer 4 and the surface layer 6 composed of fluororesin is removed by treatment using some means not shown. From the viewpoint of thermal conductivity, the thickness of the adhesive layer 5 after treatment is preferably 20 μm or less.

[0178] Then, the addition curing type silicone rubber adhesive 5 is heated by heating means such as an electric furnace for a predetermined time, thereby curing and bonding the addition curing type silicone rubber adhesive 5; and then a fixing member can be obtained by cutting both ends of the resultant product in the width direction into desired lengths.

[0179] (6) Thermal fixing equipment

[0180] The heat fixing device according to the present embodiment is constructed in such a manner that rotating members such as a pair of heating rollers, belts and rollers, belts and belts are pressed against each other. The type of the heat fixing device is appropriately selected in consideration of conditions such as the processing speed and size of the entire image forming device on which the heat fixing device is installed.

[0181] In the heat fixing device, the heated fixing member and the pressure member are pressed against each other, thereby forming a fixing nip portion N; then, the recording medium S as a heated body having an image formed by unfixed toner thereon is conveyed to and held in the fixing nip portion N. The image formed by the unfixed toner is called a toner image t. Thus, the toner image t is heated and pressurized. As a result, the toner image t melts and the colors are mixed, and then cooled, thereby fixing the image on the recording medium.

[0182] The structure of the heat fixing device will be explained below based on specific embodiments, but the scope and application of the present invention are not meant to be limited to the following embodiments.

[0183] (6-1) Fusing belt-pressure belt type heat fixing equipment

[0184] Figure 71 is a schematic cross-sectional view of an example of a so-called double-belt type heat fixing apparatus in which a pair of rotating members in the form of a fixing belt 11 and a pressing belt 12 are brought into pressure contact with each other, the heat fixing apparatus being provided with a fixing belt as a fixing member and a pressing belt as a pressing member.

[0185] The width direction of the heat fixing device or the member constituting the heat fixing device is perpendicular to Figure 7 The front of the heat fixing device is the face of the introduction side of the recording medium S. The terms "left" and "right" mean "left" and "right" when the heat fixing device is viewed from the front. The width of the belt is the dimension in the left-right direction when the device is viewed from the front. The width of the recording medium S is its dimension in the direction perpendicular to the conveying direction. The terms upstream or downstream mean upstream and downstream relative to the conveying direction of the recording medium.

[0186] The heat fixing device includes a fixing belt 11 as a fixing member and a pressure belt 12 as a pressure member. The fixing belt 11 and the pressure belt 12 are connected by passing between two rollers such as Figure 2A The fixing belt shown is constructed with a flexible substrate made of a metal whose main component is nickel.

[0187] Here, as a heating means for the fixing belt 11, a heating source (induction heating component or excitation coil) that can induce electromagnetic induction heating with high energy efficiency is used. The induction heating component 13 includes an induction coil 13a, an excitation core 13b, and a coil holder 13c that holds the above. As the induction coil 13a, an elliptical flat-wound Litz wire is used, and the induction coil 13a is arranged in a transverse E-shaped excitation core 13b with protrusions in the center and both sides of the induction coil. The excitation core 13b is composed of materials such as ferrite and permalloy that exhibit high magnetic permeability and low residual magnetic flux density, thereby being able to suppress the loss of the induction coil 13a and the excitation core 13b, and being able to efficiently heat the fixing belt 11.

[0188] When a high-frequency current flows from the excitation circuit 14 to the induction coil 13a of the induction heating member 13, the base of the fixing belt 11 generates induction heat, and the fixing belt 11 is heated from the base side. The surface temperature of the fixing belt 11 is detected by a temperature detection element 15 such as a thermistor. A signal related to the temperature of the fixing belt 11 detected by the temperature detection element 15 is sent to the control circuit section 16. The control circuit section 16 controls the power supplied from the excitation circuit 14 to the induction coil 13a in such a manner that the temperature information received from the temperature detection element 15 is maintained at a predetermined fixing temperature, thereby adjusting the temperature of the fixing belt 11 to the predetermined fixing temperature.

[0189] The fixing belt 11 is strung over a roller 17 as a belt rotating member and a heating-side roller 18. The roller 17 and the heating-side roller 18 are rotatably supported by bearings between left and right side plates of the device (not shown).

[0190] The roller 17 is, for example, a hollow iron roller having an outer diameter of 20 mm, an inner diameter of 18 mm, and a thickness of 1 mm, and is used as a tension roller for applying tension to the fixing belt 11. The heating side roller 18 is, for example, a highly slidable elastic roller having a silicone rubber layer as an elastic layer provided on an iron alloy metal core having an outer diameter of 20 mm and a diameter of 18 mm.

[0191] The heating side roller 18 as a driving roller is rotationally driven at a prescribed speed in the clockwise direction of the arrow by having a driving force input from a driving source (motor) M. By providing the elastic layer on the heating side roller 18 as described above, the driving force input to the heating side roller 18 can be satisfactorily transmitted to the fixing belt 11, and a fixing nip for ensuring the separation of the recording medium from the fixing belt 11 can be formed. Since the heating side roller 18 thus has the elastic layer, little heat is transmitted to the heating side roller; therefore, this is effective in shortening the heating time.

[0192] In the rotational drive of the heating side roller 18, the fixing belt 11 rotates together with the roller 17 due to the friction between the silicone rubber surface of the heating side roller 18 and the inner surface of the fixing belt 11. The arrangement and size of the roller 17 and the heating side roller 18 are selected according to the size of the fixing belt 11. For example, the sizes of the roller 17 and the heating side roller 18 are selected in such a manner that the fixing belt 11 having an inner diameter of 55 mm when not attached can span around the rollers.

[0193] The pressure belt 12 spans between a tension roller 19 and a pressure side roller 20 as belt rotating members. The inner diameter of the pressure belt when not attached is, for example, 55 mm. The tension roller 19 and the pressure side roller 20 are rotatably supported on bearings between the left and right sides of the device, not shown.

[0194] The tension roller 19 has, for example, a silicone sponge layer provided on an iron alloy metal core having an outer diameter of 20 mm and a diameter of 16 mm to reduce heat conduction from the pressure belt 12 .

[0195] The pressure side roller 20 is a rigid roller composed of, for example, a 2 mm thick iron alloy with an outer diameter of 20 mm and an inner diameter of 16 mm, and exhibits low sliding properties. The dimensions of the tension roller 19 and the pressure side roller 20 are similarly selected in accordance with the dimensions of the pressure belt 12 .

[0196] To form the nip N between the fixing belt 11 and the pressure belt 12 , the pressure-side roller 20 is pressed against the heating-side roller 18 by a predetermined pressure applied in the arrow F direction by a pressure mechanism not shown.

[0197] In order to obtain a wide roller gap N without increasing the size of the device, a pressure pad is used. Specifically, a fixing pad 21 as a first pressure pad presses the fixing belt 11 toward the pressure belt 12, and a pressure pad 22 as a second pressure pad presses the pressure belt 12 toward the fixing belt 11. The fixing pad 21 and the pressure pad 22 are supported between the left and right side plates of the device, which are not shown. The pressure pad 22 presses the fixing pad 21 in the direction of the arrow G with a predetermined pressure by a pressure mechanism, which is not shown. The fixing pad 21 as the first pressure pad has a pad base and a sliding sheet (low friction sheet) 23 in contact with the belt. The pressure pad 22 as the second pressure pad also has a sliding sheet 24 in contact with the pad base and the belt. This is because the problem arises when the portion of the pad that rubs against the inner peripheral surface of the belt experiences significant wear. Thus, by sandwiching the sliding sheets 23 and 24 between the belt and the pad base, the pad wear can be prevented and the sliding resistance can be reduced, resulting in ensuring good belt running performance and belt durability.

[0198] The fixing belt is provided with a non-contact type anti-static brush (not shown), and the pressure belt is provided with a contact type anti-static brush (not shown).

[0199] The control circuit section 16 drives the motor M at least during the execution of image formation. As a result, the heating side roller 18 is rotationally driven, and the fixing belt 11 is also rotationally driven in the same direction. The pressure belt 12 rotates along with the fixing belt 11. By configuring the most downstream portion of the fixing nip in such a manner that the fixing belt 11 and the pressure belt 12 are conveyed while being sandwiched by the roller pair 18, 20, belt slippage can be prevented. The most downstream portion of the fixing nip is a portion in which the pressure distribution (in the conveying direction of the recording medium) is the largest in the fixing nip.

[0200] In a state where the fixing belt 11 is raised to and maintained at a predetermined fixing temperature (referred to as temperature control), the recording medium S having an unfixed toner image t is conveyed to the nip N between the fixing belt 11 and the pressure belt 12. The recording medium S is introduced in such a manner that the surface bearing the unfixed toner image t faces the fixing belt 11. Since the unfixed toner image t of the recording medium S is conveyed while being sandwiched in close contact with the outer peripheral surface of the fixing belt 11, heat is applied thereto from the fixing belt 11, which heat is combined with the received pressure, so that the toner image t is fixed to the surface of the recording medium S. At this time, the heat from the heated base of the fixing belt 11 is effectively transferred toward the recording medium S through the elastic layer having increased thermal conductivity in the thickness direction. Thereafter, the recording medium S is separated from the fixing belt by the separation member 25 to be further conveyed.

[0201] (6-2) Thermal fixing device of fixing belt-pressure roller type

[0202] Figure 8 is a schematic diagram showing an example of a fixing belt-pressure roller type heat fixing device using a ceramic heater as a heating element. Figure 8 In the figure, reference numeral 11 denotes a tubular or endless fixing belt; here, an endless fixing belt such as that described above is used. The apparatus has a heat-resistant and heat-insulating belt guide 30 for holding the fixing belt 11, and a ceramic heater 31 for heating the fixing belt 11, which is fixed and supported at a position in contact with the fixing belt 11 (i.e., at a substantially central portion of the lower surface of the belt guide 30) by being embedded in a groove formed along the length of the guide. The fixing belt 11 is loosely embedded around the belt guide 30. A pressurizing rigid stay 32 is inserted inside the belt guide 30.

[0203] A pressure roller 33 is provided opposite to the fixing belt 11. In this example, the pressure roller is an elastic pressure roller, that is, an elastic layer 33b of silicone rubber is provided on a metal core 33a having a reduced hardness, because both ends of the metal core 33a are rotatably held between the front and rear chassis side plates of the device, not shown. The elastic pressure roller is coated with a PFA (tetrafluoroethylene / perfluoroalkyl ether copolymer) tube for the purpose of improving the surface property.

[0204] By providing respective pressurizing springs (not shown) between the spring receiving member (not shown) on the side of the apparatus chassis and both ends of the pressurizing rigid stay 32, a downward urging action is applied to the pressurizing rigid stay 32. As a result, the lower surface of the ceramic heater 31 disposed on the lower surface of the belt guide member 30 made of a heat-resistant resin and the upper surface of the pressurizing roller 33 are pressed against each other with the fixing belt 11 sandwiched therebetween, thereby forming a fixing nip portion N.

[0205] The pressure roller 33 is rotationally driven in the counterclockwise direction indicated by the arrow by a driving means not shown. With the rotational drive from the pressure roller 33, a rotational force acts on the fixing belt 11 due to the frictional force between the outer surface of the fixing belt 11 and the pressure roller 33; as a result, the inner surface of the fixing belt 11 slides in close contact with the lower surface of the ceramic heater 31 at the fixing roller nip portion N, while rotating in the clockwise direction indicated by the arrow around the outside of the belt guide 30 at a circumferential speed substantially corresponding to the rotational circumferential speed of the pressure roller 33 (pressure roller driving scheme).

[0206] Based on the print start signal, the pressure roller 33 starts to rotate, and the ceramic heater 31 starts to heat. The rotational circumferential speed of the fixing belt 11 is constant due to the rotation of the pressure roller 33, so that the temperature of the temperature detection element 34 provided on the top surface of the ceramic heater rises to a predetermined temperature, for example, 180° C., and the recording medium S carrying the unfixed toner image t as the heated material is introduced between the fixing belt 11 and the pressure roller 33 at the fixing nip portion N in such a manner that the toner image carrying surface side faces the fixing belt 11. The recording medium S comes into close contact with the lower surface of the ceramic heater 31 across the fixing belt 11 at the fixing nip portion N, and moves through the fixing nip portion N together with the fixing belt 11. During this movement, heat from the fixing belt 11 is applied to the recording medium S, and thereby the toner image t becomes thermally fixed on the surface of the recording medium S. The recording medium S having passed through the fixing nip portion N is separated from the outer surface of the fixing belt 11 to be further conveyed.

[0207] The ceramic heater 31 as a heating element is a linear heating element having a low heat capacity and being elongated in a direction perpendicular to the moving direction of the fixing belt 11 and the recording medium S. Preferably, the basic structure of the ceramic heater 31 includes: a heater substrate 31a composed of aluminum nitride or the like; a heat generating layer 31b disposed longitudinally on the surface of the heater substrate 31a, the heat generating layer 31b being obtained by, for example, applying a resistive material such as Ag / Pd (silver / palladium) of about 10 μm on a width of 1 to 5 mm by screen printing; and a protective layer 31c of glass, fluorine resin or the like further disposed on the heat generating layer 31b. The ceramic heater used is not limited to the above-mentioned type of ceramic heater.

[0208] As a result of electricity being supplied to both ends of the heat generating layer 31 b of the ceramic heater 31 , the heat generating layer 31 b generates heat, so that the temperature of the heater 31 rises rapidly.

[0209] The ceramic heater 31 is fixed and supported by being embedded in a groove formed along the length of the guide at a substantially central portion of the lower surface of the belt guide 30 with the protective layer 31c side facing upward. At the fixing nip portion N in contact with the fixing belt 11, the surface of the sliding member 31d of the ceramic heater 31 and the inner surface of the fixing belt 11 slide against each other while contacting each other.

[0210] In the fixing belt 11, as described above, the thermal conductivity in the thickness direction of the elastic layer containing silicone rubber is improved, and the hardness is also kept low. In such a configuration, the fixing belt 11 can effectively heat the unfixed toner image while showing low hardness, and as a result, a high-quality image can be fixed on the recording medium S at the time of fixing nip.

[0211] As described above, one aspect of the present disclosure provides a heat fixing device having a fixing member disposed thereon. Therefore, a heat fixing device having a fixing member having excellent fixing performance and excellent image quality disposed therein can be provided.

[0212] Example

[0213] The present invention will be explained in more detail below by way of examples. However, the present disclosure is not limited to these examples. Hereinafter, the term "part" means "part by mass".

[0214] [Example 1]

[0215] (1) Preparation of liquid addition-curing silicone rubber composition

[0216] As component (a), 100 parts by mass of an organosilicon polymer was first prepared, which had vinyl groups as unsaturated aliphatic groups only at both ends of the molecular chain and methyl groups as unsubstituted hydrocarbon groups, and did not contain other unsaturated aliphatic groups. The organosilicon polymer (product name: DMS-V35, manufactured by Gelest Inc., viscosity 5000 mm 2 / s) will be referred to as "Vi" hereinafter.

[0217] Next, 124 parts by mass of large-diameter metallic silicon (product name: #350, Kinsei Matec Co., Ltd.) and 41 parts by mass of small-diameter metallic silicon (product name: FINE, Kinsei Matec Co., Ltd.) were added to the Vi as component (d), and the whole was placed in a rotary / rotating mixer (ARV-310, Thinky Corporation), and stirred and mixed at 2000 rpm for 4 minutes to obtain a mixture 1.

[0218] Then, 0.2 parts by mass of 1-ethynyl-1-cyclohexanol (manufactured by Tokyo Chemical Industry Co., Ltd.) as a curing retardant dissolved in the same weight of toluene was added to Mixture 1 to obtain Mixture 2.

[0219] Next, 0.1 parts by mass of component (c) in the form of a hydrosilylation catalyst (platinum catalyst: a mixture of 1,3-divinyltetramethyldisiloxane platinum complex, 1,3-divinyltetramethyldisiloxane, and 2-propanol) was added to mixture 2 to obtain mixture 3.

[0220] 1.1 parts by mass of component (b) in the form of a straight-chain siloxane skeleton of an organosilicon polymer having silicon-bonded active hydrogen groups only on the side chains (product name: HMS-301, manufactured by Gelest Inc., viscosity 30 mm 2 / s, hereinafter referred to as "SiH"). Component (b) is added to mixture 3 and mixed thoroughly to obtain a liquid addition curing silicone rubber composition. Here, the blending amount of the thermally conductive filler (component (d)) relative to the silicone rubber is 40 vol%.

[0221] (2) Production of fixing belts

[0222] Here, a SUS endless belt having an inner diameter of 24 mm, a width of 400 mm, and a thickness of 30 μm was prepared as a substrate. During the production step, the endless belt was processed by inserting a core into the inside thereof.

[0223] A primer (product name: DY39-051A / B; manufactured by Dow Corning Toray Co., Ltd.) was roughly evenly applied to the outer peripheral surface of the substrate in a manner such that the dry weight of the primer was 20 mg; after drying the solvent, the primer was baked in an electric oven set at 160°C for 30 minutes.

[0224] The above silicone rubber composition was applied to the resulting primer-treated substrate by ring coating at a thickness of 250 μm. The resulting product was referred to as an uncured ring belt.

[0225] Next, corona charging devices with a charging area width of 295 mm were placed opposite to each other along the generatrix of the uncured endless belt, and an AC electric field was applied to the surface of the elastic layer before curing while the uncured endless belt was rotated at 100 rpm. The conditions for corona discharge included a current of ±150 μA supplied to the discharge wire of the corona charging device, a grid electrode potential of ±300 V (Vp-p: 600 V), a frequency of 0.025 Hz, a charging time of 160 seconds, and a distance of 3 mm between the grid electrode and the belt.

[0226] The charged uncured endless belt is heated in an electric furnace at 160°C for 1 minute (primary curing), and then heated in an electric oven at 200°C for 30 minutes (secondary curing) to cure the silicone rubber composition, and then heated in a vacuum drying oven at 330°C for 5 minutes to obtain an endless belt provided with an elastic layer.

[0227] Next, an addition-curing silicone rubber adhesive (product name: SE1819CV A / B; Dow Corning Toray Industries, Inc.) was applied roughly uniformly as an adhesive layer to the surface of the cured elastic layer of the endless belt to a thickness of about 10 μm. A fluororesin tube (product name: NSE, manufactured by Gunze Limited) having an inner diameter of 23 mm and a thickness of 20 μm was covered on the belt as a peeling layer while widening the diameter of the tube. Then, the belt surface was uniformly processed from above the fluororesin tube, thereby removing excess adhesive from between the elastic layer and the fluororesin tube, and thinning the adhesive to about 5 μm.

[0228] The endless belt was heated for 1 hour in an electric oven set at 200° C., so that the adhesive was cured, thereby fixing the fluororesin tube to the elastic layer. Both ends of the obtained endless belt were cut off to obtain a fixing belt with a width of 336.5 mm.

[0229] (3) Evaluation of properties of the elastic layer of the fixing belt

[0230] (3-1) Thermal conductivity in the thickness direction of the elastic layer

[0231] The thermal conductivity λ in the thickness direction of the elastic layer is calculated based on the following formula:

[0232] λ=α×Cp×ρ

[0233] Where λ represents the thermal conductivity of the elastic layer in the thickness direction (W / (m·K)), and α represents the thermal diffusivity in the thickness direction (m 2 / s), Cp represents the specific heat at constant pressure (J / (kg·K)), and ρ represents the density (kg / m 3 The values ​​of thermal diffusivity α in the thickness direction, specific heat at constant pressure Cp and density ρ were calculated as follows.

[0234] - Thermal diffusivity α

[0235] At room temperature (25°C), the thermal diffusivity α of the elastic layer in the thickness direction was measured using a cycle heating method thermal property measuring device (product name: FTC-1, Advance Riko Inc.). Sample pieces with a surface area of ​​8 mm × 12 mm were cut out from the elastic layer using a cutter, and a total of 5 sample pieces were prepared; a digital end measuring machine (product name: DIGIMICRO (registered trademark) MF-501 flat probe Nikon Corporation) measured the thickness of each sample piece. Then, each sample piece was measured 5 times in total and the average value (m 2 / s). The sample piece was measured while being pressed with a weight of 1 kg.

[0236] Therefore, the thermal diffusivity α of the silicone rubber elastic layer in the thickness direction is 9.96×10 -7 m 2 / s.

[0237] -Specific heat at constant pressure Cp

[0238] The constant-pressure specific heat of the elastic layer was measured using a differential scanning calorimeter (product name: DSC823e, Mettler-Toledo International Inc.).

[0239] Specifically, each aluminum pan is used as a sample pan and a reference pan. First, as a blank measurement, the measurement is performed according to the following procedure, the two pans in an empty state are kept at a constant temperature of 15°C for 10 minutes, and then the pans are heated to 215°C at a heating rate of 10°C / min, and the pans are kept at a constant temperature of 215°C for another 10 minutes. Next, using 10 mg of synthetic sapphire with known constant pressure specific heat, the measurement is performed according to the same procedure. Next, a 10 mg measurement sample of the same amount as the reference material synthetic sapphire is cut out from the elastic layer, placed in a sample pan, and measured according to the same procedure. These measurement results are analyzed using the specific heat analysis software attached to the above-mentioned differential scanning calorimeter, and the constant pressure specific heat Cp at 25°C is calculated from the average value of the 5 measurement results.

[0240] As a result, the constant-pressure specific heat of the elastic layer of the silicone rubber was 1.05 J / (g·K).

[0241] -density ρ

[0242] The density of the elastic layer was measured using a dry automatic densitometer (product name: AccuPyc 1330-01, Shimadzu Corporation). 3 A sample cell is provided; and a sample piece is cut out from the elastic layer to fill about 80% of the cell volume, the mass of the sample piece is measured, and then the sample piece is loaded into the sample cell. The sample cell is set in a measurement part in the apparatus; helium is used as a measurement gas, and then the volume is measured 10 times after gas purging. For each measurement, the density of the elastic layer is calculated from the mass of the sample piece and the measured volume to calculate an average value.

[0243] As a result, the density of the silicone rubber elastic layer was 1.53 g / cm 3 .

[0244] The thermal conductivity λ in the thickness direction of the elastic layer is calculated from the constant pressure specific heat Cp (J / (kg·K)) in the conversion unit and the density ρ (kg / m 3 ) and thermal diffusivity α(m 2 / s); as a result, the thermal conductivity λ is 1.60 W / (m·K).

[0245] (3-2) Compression modulus of elastic layer

[0246] The compression modulus in the thickness direction of the elastic layer was measured using a dynamic viscoelasticity measuring device (product name: Rheogel-E4000, manufactured by UBM Co., Ltd.). Specifically, a test piece with an area of ​​50×50 mm was cut out from the elastic layer using a cutter. The test piece was subjected to 5 compression tests in the thickness direction of the elastic layer under conditions including a frequency of 1 Hz, a strain of 0.05 mm, and an initial strain of 0.02 mm, and the arithmetic mean of the measured values ​​obtained in the test was calculated. The average value was regarded as the compression modulus in the thickness direction of the elastic layer.

[0247] (3-3) Tensile modulus of elastic layer

[0248] In order to check that the elastic layer has low hardness, the tensile modulus of the elastic layer is measured. Specifically, a dumbbell-shaped measurement specimen No. 8 in accordance with Japanese Industrial Standard (JIS) K6251: 2004 is made from the elastic layer using a punching die. Here, the length direction of the specimen is set to be parallel to the thickness direction ( Figure 6B The direction perpendicular to the arrow 601) ( Fig. 6A Specifically, the length direction of the sample ( Fig. 6A The direction perpendicular to the circumferential direction of the fixing belt (arrow 603 in the figure) and the direction perpendicular to the circumferential direction of the fixing belt (direction along the rotation axis) are set to be substantially consistent with each other. The thickness near the center as the measurement location is measured. Next, a tensile tester (equipment name: Strograph EII-L1, manufactured by Toyo Seiki Seisakusho Ltd.) is used to measure the thickness of the elastic layer in the direction perpendicular to the thickness direction of the elastic layer, i.e., Fig. 6A The test specimen is tested at room temperature at a tensile speed of 200 mm / min in the direction of the middle arrow 603. A graph is then created from the measurement results, with the strain of the specimen on the horizontal axis and the tensile stress on the vertical axis; the slope of the linear approximation of the measured data in the strain range of 0 to 10% is considered the tensile modulus.

[0249] As a result, the tensile modulus of the elastic layer was 0.15 MPa.

[0250] (3-4) Change in hardness of the elastic layer when left at rest in an atmosphere at 240°C

[0251] A rectangular parallelepiped sample of 50 mm in length, 50 mm in width, and 150 μm in thickness sampled from the elastic layer using a cutter was left to stand for 100 hours in an atmosphere at a temperature of 240°C and an oxygen concentration of 1% or less, and the compression modulus of the sample in the thickness direction was measured three times every 10 hours; here, H10 to H100 were taken as the respective average values ​​of the measurements, and the reduction rate of each of the compression moduli H10 to H100 relative to the compression modulus H0 at 0 hours as a reference was measured. Specifically, in order to reduce the oxygen concentration to less than 1%, the inside of an oven connected to a vacuum pump was reduced to less than 0.01 atmospheres, and then an inert gas was injected. In order to suppress oxidation caused by atmosphere exchange when loading and unloading the sample, each sample was wrapped in aluminum foil and loaded into / unloaded from the oven in this way.

[0252] (4) Actual machine evaluation (fixing performance, durability, image quality)

[0253] <Evaluation of Fixing Performance>

[0254] use Figure 8 The fixing performance of the fixing belt-pressure roller heating type fixing device with the produced fixing film built therein was evaluated. The pressure roller was driven to rotate at a moving speed (circumferential speed) of 320 mm / sec on the surface of the pressure roller under a state where the pressure from one end was about 156.8 N and the total pressure was about 313.6 N (32 kgf); then, the surface temperature of the fixing film in the paper passing portion was controlled at 150°C to 180°C, and the fixing film was rotated at a base weight of 81 g / m 2 A cyan solid image is formed on plain paper (product name: GF-C081, manufactured by Canon Inc.).

[0255] Specifically, the fixing temperature of the heat fixing device was adjusted from 150°C to 160°C as the standard fixing temperature of the above-mentioned copier, five cyan solid images were formed continuously, and the image density of the fifth solid image was measured. Next, lens cleaning paper was used to apply 4.9 kPa (50 g / cm 2 The toner surface of the solid image was rubbed three times in the same direction under a load of 100 % and the image density after rubbing was measured. In the case where the reduction rate of the image density before and after rubbing (=[image density difference before and after rubbing / image density before rubbing]×100) was less than 5%, it was determined that the toner had been fixed to the thick paper. The results were evaluated according to the following criteria. The image density was measured using a reflection densitometer (Macbeth Corporation).

[0256] A: Toner is fixed to paper at a fixing temperature of 150°C to lower than 155°C.

[0257] B: Toner is fixed to paper at a fixing temperature of 155°C to lower than 160°C.

[0258] C: Toner is fixed to paper at a fixing temperature of 160° C. or higher.

[0259] <Durability Evaluation>

[0260] The fixing temperature was set to the standard fixing temperature (160° C.), a cyan solid image was continuously formed on A4-sized plain paper, the number of prints at the time point when the elastic layer of the fixing belt broke or plastically deformed was recorded, and then the durability was evaluated according to the following criteria. Even when the print count reached 740,000, no breakage or plastic deformation occurred in the elastic layer of the fixing belt, and thus the image formation was stopped at 740,000 prints.

[0261] A: Even upon image formation on 740,000 prints, no breakage or plastic deformation was observed in the elastic layer of the fixing belt.

[0262] B: Even in the image formation on 600,000 prints, no breakage or plastic deformation occurred in the elastic layer of the fixing belt, but in the image formation on 740,000 prints, breakage or plastic deformation occurred in the elastic layer of the fixing belt.

[0263] C: As a result of image formation on less than 600,000 prints, breakage or plastic deformation occurred in the elastic layer of the fixing belt.

[0264] <Image Quality Evaluation (Evaluation of Melting Unevenness)>

[0265] An index of the followability of the fixing member to the unevenness of the paper can be obtained by observing the melting state of the toner after fixing the toner image that has been formed on the paper.

[0266] Using a film heating type fixing device 40 similar to the durability evaluation, 10 images for evaluation of fusion unevenness were continuously fixed in an environment of a temperature of 10° C. and a relative humidity of 50%. The paper used here was A4 size recycled paper (product name: Recycled Paper GF-R100; manufactured by Canon Inc., thickness 92 μm, basis weight 66 g / m 2 , waste paper content 70%, Bekker smoothness 23 seconds (according to the method of JIS P8119). The melting unevenness evaluation image is an image in which a 10 mm×10 mm patch image formed of 100% density cyan toner and magenta toner is arranged near the center of the paper surface.

[0267] Here, the scale of melting unevenness is color mixing by toner melting, which is caused by applying sufficient heat and pressure to the image portion where two colors are formed. In particular, in the case where heat is applied to the concave part of the paper relief without applying pressure, the residual grain boundaries of the toner continue to exist after fixing, resulting in melting unevenness in a state where color mixing is not fully achieved. In the case where the fixing member cannot fully adapt to the paper concave and convex, color mixing occurs in the convex part where pressure acts, but is insufficient in the concave part. Therefore, the concave and convex followability is determined by observing the melting state of the image forming area.

[0268] After 10 images for evaluating melting unevenness were printed continuously, the 10th sample was taken out, and the image formation area was observed under an optical microscope to evaluate melting unevenness. The evaluation criteria were as follows.

[0269] Evaluation Benchmarks

[0270] A: Even in the concave parts of paper fibers, toner particle boundaries are not visible at all; colors are mixed in the convex parts and the concave parts.

[0271] B: Some toner particle boundaries were observed in the concave portions of paper fibers, but most of the toner particles were mixed in the convex portions and concave portions.

[0272] C: Color mixing occurs only in the convex portions of paper fibers, and many toner particle boundaries are observed in the concave portions.

[0273] [Example 2]

[0274] A fixing belt was produced and evaluated in the same manner as in Example 1 except that the electric field orientation time was set to 10 seconds.

[0275] [Example 3]

[0276] A fixing belt was produced and evaluated in the same manner as in Example 1, except that during the formation of the elastic layer, the silicone rubber composition was cured by heating at 200° C. for 30 minutes in an electric furnace (secondary curing), and the temperature at the high-temperature heating treatment performed thereafter was 280° C.

[0277] [Example 4]

[0278] A fixing belt was produced and evaluated in the same manner as in Example 1 except that 103 parts by mass of large-diameter metallic silicon (product name: #350, Kinsei Matec Co., Ltd.) and 62 parts by mass of small-diameter metallic silicon (product name: FINE, Kinsei Matec Co., Ltd.) were added thereto.

[0279] [Example 5]

[0280] A fixing belt was produced and evaluated in the same manner as in Example 1 except that 177 parts by mass of large-diameter metallic silicon (product name: #350, Kinsei Matec Co., Ltd.) and 12 parts by mass of small-diameter metallic silicon (product name: FINE, Kinsei Matec Co., Ltd.) were added thereto.

[0281] [Comparative Example 1]

[0282] A fixing belt was produced and evaluated in the same manner as in Example 1, except that the amount of the crosslinking agent (SiH) was set to 1.4 parts herein.

[0283] [Comparative Example 2]

[0284] A fixing belt was produced and evaluated in the same manner as in Example 1 except that the electric field orientation treatment was not performed here.

[0285] [Comparative Example 3]

[0286] A fixing belt was produced and evaluated in the same manner as in Example 1 except that during the formation of the elastic layer, heating was performed in an electric furnace at 200° C. for 30 minutes (secondary curing) to cure the silicone rubber composition and no high-temperature heating treatment was performed thereafter.

[0287] The above results are given in Tables 1 and 2.

[0288] [Table 1]

[0289] Table 1

[0290]

[0291] [Table 2]

[0292] Table 2

[0293]

[0294] In Tables 1 and 2, the value of "Hardness Change" shows the change result of the hardness change when the elastic layer is left to stand in an atmosphere at 240° C., and represents the reduction rate of the values ​​of the compression modulus H10 to H100 per 10 hours relative to the value of the compression modulus H0 at 0 hours. A negative value of the reduction rate indicates that the compression modulus has increased relative to H0.

[0295] Good results of A or B in fixing performance, durability and image quality were obtained in all Examples. The lower the tensile modulus, the better the image quality; in addition, the lower the tensile modulus / compression modulus ratio, the higher the thermal conductivity, and the better the fixing performance.

[0296] In contrast, in the comparative examples, a result of rank C was obtained in any one of the items of fixing performance, durability, and image quality.

[0297] As described above, the present disclosure can be used as an electrophotographic member that provides a low hardness state while ensuring thermal conductivity and durability in the thickness direction of the elastic layer of the fixing member.

[0298] While the present invention has been described with reference to exemplary embodiments, it is to be understood that the invention is not limited to the disclosed exemplary embodiments.The scope of the following claims is to be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures and functions.

Claims

1. An electrophotographic member comprising: matrix, and an elastic layer on the outer peripheral surface of the substrate; in The elastic layer comprises silicone rubber, The tensile modulus of the elastic layer in a direction perpendicular to its thickness direction is 0.20 MPa or less, The compression modulus of the elastic layer in the thickness direction is 0.19 to 0.57 MPa, The ratio of the tensile modulus of the elastic layer in a direction perpendicular to the thickness direction to the compressive modulus of the elastic layer in the thickness direction, that is, tensile modulus / compressive modulus, is 0.80 or less. When the compression moduli H0 to H100 are respective values ​​of the compression moduli in a direction corresponding to the thickness direction of the elastic layer at intervals of 10 hours up to 100 hours in an atmosphere at a temperature of 240° C. and an oxygen concentration of 1% or less and taken as a rectangular parallelepiped sample of 50 mm in length, 50 mm in width, and 150 μm in thickness, the reduction rate of each of the compression moduli H10 to H100 with respect to the compression modulus H0 serving as a reference is 5% or less. 2 . The electrophotographic member according to claim 1 , wherein the silicone rubber comprises a cured product of an addition-curing silicone rubber composition.

3. The electrophotographic member according to claim 1 or 2, wherein In using the elastic layer as a sample 29 In the graph obtained in Si-NMR measurement, the ratio of the integrated value of the peak corresponding to the T unit to the integrated value of the peak corresponding to the D unit, that is, T unit / D unit, is 0.030 or more. 4 . The electrophotographic member according to claim 1 , wherein when the silicone rubber is heated at 150° C. for 1 hour, a total generated amount of hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane and decamethylcyclopentasiloxane is 1.5 ppm or more. 5 . The electrophotographic member according to claim 1 , wherein the elastic layer contains a filler, and a content of the filler in the elastic layer is 30 vol % to less than 50 vol % relative to the silicone rubber.

6. The electrophotographic member according to claim 5, wherein In the case of a binary image of 150 μm×100 μm obtained at 5 locations in a first cross section in the thickness-circumferential direction of the elastic layer, and in the case of a binary image of 150 μm×100 μm obtained at 5 locations in a second cross section in the thickness-axial direction of the elastic layer, the average area ratio of the large particle filler having a circle equivalent diameter of 5 μm or more in a total of 10 binary images is 20 to 40%, The average arrangement degree fL of the large particle filler is 0.00-0.15, The average area ratio of the small particle fillers with a circle equivalent diameter less than 5 μm in the binary image is 10-20%. The average arrangement degree fS of the small particle filler is 0.20 to 0.50, and The average arrangement angle ΦS of the small particle filler is 60° to 120°.

7. The electrophotographic member according to claim 1 or 2, wherein the electrophotographic member is a fixing member having a ring-shaped shape.

8. The electrophotographic member according to claim 1 or 2, wherein the electrophotographic member is a pressing member having a ring-shaped shape.

9. A heat fixing device in an electrophotographic image forming device, the heat fixing device comprising: A fixing member and a pressure member arranged opposite to the fixing member, wherein At least one of the fixing member and the pressing member is an electrophotographic member according to any one of claims 1 to 8.

10. An electrophotographic image forming apparatus comprising a heat fixing apparatus, wherein The heat fixing device includes a fixing member and a pressing member arranged opposite to the fixing member, and At least one of the fixing member and the pressing member is an electrophotographic member according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Fixing member and fixing device

    JP2005300591A

  • Fixing member and thermal fixing device

    JP2019215531A